2023
DOI: 10.3389/fneur.2023.1110298
|View full text |Cite
|
Sign up to set email alerts
|

Lasting alteration of spatial orientation induced by passive motion in rabbits and its possible relevance to mal de débarquement syndrome

Abstract: BackgroundMal de débarquement syndrome (MdDS) is a chronic disorder of spatial orientation with a persistent false sensation of self-motion, whose onset typically follows prolonged exposure to passive motion of a transport vehicle. Development of similar but transient after-sensations mimicking the exposed motion and associated postural instability, indicative of central vestibular adaptation, are common. The cause of MdDS is thought to be a subsequent failure to readapt to a stationary environment. However, v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 89 publications
(90 reference statements)
1
3
0
Order By: Relevance
“…The results revealed that, following conditioning, an unusual ocular drift occurred in the yaw plane during rolling maneuvres, moving in the opposite direction to the nystagmus observed during conditioning. This finding suggests a maladaptive alteration and emphasizes the value of this rabbit model in MdDS research (12).…”
Section: The Cause Of the Mal De Debarquement Syndromesupporting
confidence: 51%
See 2 more Smart Citations
“…The results revealed that, following conditioning, an unusual ocular drift occurred in the yaw plane during rolling maneuvres, moving in the opposite direction to the nystagmus observed during conditioning. This finding suggests a maladaptive alteration and emphasizes the value of this rabbit model in MdDS research (12).…”
Section: The Cause Of the Mal De Debarquement Syndromesupporting
confidence: 51%
“…Nineteen patients came back for a second treatment session, six for a third, and five for a fourth. From the 101 individual patients, 81 are female of on average (SD) 45 (15) years old and between 18 and 79 years of age, and 20 male of on average (SD) 39 (12) years old and between 24 and 61 years of age. Patients had had complaints for a median (median absolute deviation (MAD)) of 3.7 (1.78) years and between 1 month and 21 years, before they received the OKS treatment.…”
Section: Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further support for the velocity storage involvement in MdDS comes from a sham-controlled study, which demonstrated a treatment effect when head tilts were coupled with large-field visual motion as in the original protocol but not with a non-moving but otherwise identical visual pattern (45). A recent sequel animal-based study also supports that the effect of VOR maladaptation can be systematically cumulated or reversed by the choice of the vestibular stimulus (46). Together, VOR readaptation has come to be recognized as the first effective treatment for MdDS (47).…”
Section: Introductionmentioning
confidence: 95%